2016
DOI: 10.5194/nhess-16-2697-2016
|View full text |Cite
|
Sign up to set email alerts
|

The drought risk of maize in the farming–pastoral ecotone in Northern China based on physical vulnerability assessment

Abstract: Abstract. Climate change is affecting every aspect of human activities, especially the agriculture. In China, extreme drought events caused by climate change have posed a great threat to food safety. In this work we aimed to study the drought risk of maize in the farming-pastoral ecotone in Northern China based on physical vulnerability assessment. The physical vulnerability curve was constructed from the relationship between drought hazard intensity index and yield loss rate. The risk assessment of agricultur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Here, we found that the law of physiological indexes of tomato changed with comprehensive intensity of HTHH, and the goodness of fit of all the curves was at the 0.01 significance level (Figure 6). In many previous studies, this kind of relationship was commonly called vulnerability curve, which can be used to assess the sensitivity and adaptability of a hazard-bearing body to adverse effects (Yue et al, 2015;Wang et al, 2016;Cui et al, 2019;Li et al, 2021). It is also an important part of disaster risk assessment.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Here, we found that the law of physiological indexes of tomato changed with comprehensive intensity of HTHH, and the goodness of fit of all the curves was at the 0.01 significance level (Figure 6). In many previous studies, this kind of relationship was commonly called vulnerability curve, which can be used to assess the sensitivity and adaptability of a hazard-bearing body to adverse effects (Yue et al, 2015;Wang et al, 2016;Cui et al, 2019;Li et al, 2021). It is also an important part of disaster risk assessment.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…DSSAT models have been used extensively to evaluate the impact of drought on agriculture. Most use meteorological factors in combination with the yield to evaluate the impacts of drought [31,66]. Itoh et al [67] used the DSSAT to simulate the yield changes in winter wheat and then investigated the correlations between the yield and the standardized precipitation evapotranspiration index (SPEI) and soil moisture deficit index (SMDI).…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Currently, the commonly used crop growth models include the FAO Crop Model to Simulate Yield Response to Water (AquaCrop) [27,28], Agricultural Production Systems Simulator (APSIM) [29], Environmental Policy-Integrated Climate (EPIC) [30][31][32] and Decision Support System for Agrotechnology Transfer (DSSAT) [33,34] models. Scholars use appropriate crop growth models to evaluate agricultural drought vulnerability according to the major crops in the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were extensive literatures about risk assessment and zoning of agricultural meteorological disasters, e.g., flood, drought, and chilling/freezing, focusing on the probabilistic risk assessment model [19][20][21] , hazard risk or vulnerability of hazard-affected body [22][23][24][25][26] , and corresponding risk indices [27][28][29] . Current works about crop waterlogging mainly focused on the symptom identification and corresponding indices, influences on crop yields [30][31][32] , biochemical mechanism, variety screening, and genetic improvement [11,[33][34][35] .…”
Section: Introductionmentioning
confidence: 99%